WIRENG KALANA TOPENG DI ISTANA MANGKUNEGARAN SURAKARTA - Suharji Suharji (Institut Seni Indonesia Surakarta, 2012)
Kalana Topeng at Mangkunegaran Palace called as wireng based on its heroism traits. Wireng Topeng Kalana included in heroic dance that represent personality of character who falling in love. Wireng Kalana Mangkunegaran is affected by its leadership spirit with glorious, authority, assertive, and energetic traits. Wireng Kalana Mangkunegaran has heroism traits. As one of single dances, it often accompanied with Javanese gamelan music sound Laras Pelog Patet 6, gendhing Pathetan, Ada-ada Greget Saut Sampak, Liwung, Ladrang Pucung Rubuh, Lancaran Bendrong, Ladrang Eling-eling Wantah and Sampak. There is topeng (mask) for make up. The wardrobe especially for head cover uses tekes malang, sumping, shoulder brace, bracelet, and ring. It also uses necklace in kace motive with pendok on back, complete clothes with red cinde pants, fabrics in rapekan, timing epek, boro samir and sampur model. There is binggel for ankle. Kalana character has rugged and awkward traits. The dance is begun with maju beksan, main beksan, and mundur beksan. Key words : wireng, topeng, kalana, Mangkunegaran